Perbedaan Pengetahuan dan Konsumsi Sugar-Sweetened Beverages (SSBs) pada Remaja Gizi Lebih dan Normal di MAN 2 Surakarta - Teguh, Ivan Panji, Susi Dyah Puspowati, M.Si, Luluk Ria Rakhma, S.Gz., M.Gizi (2016)
Introduction: The excessive consumption of SSBs leads to problem of overweight and obesity. The lack of nutritional knowledge was one of causes which has emerged nutritional problems and the adolescents' dynamic habit in food and beverage consumption. Objectives: This study was aimed to find out the difference between knowledge of SSBs and its consumption in overweight and normal weight adolescents on Islamic Senior High School 2 Surakarta. Research Method: This study was an observational research with cross sectional approach. The subject of this study was 64 students which were chosen by using simple random sampling method. The data of knowledge and SSBs consumption were obtained through interview by using a questionnaire food diary and nutritional status data which derived from the body mass index (BMI)-for-age. The data were analyzed using Mann-whitney test and independent t-test. Result: In the 'good' level of knowledge, the normal weight nutritional status is higher with 87.5% than the overweight nutritional status (78.12%). The frequency of SSBs consumption with 'often' category is higher in overweight nutritional status (37.5%) than normal weight nutritional status (31.3%). The overweight and normal weight had enough energy supply which is 100% respectively. Mann-whitney test result for SSBs knowledge with nutritional status, indicates p value is 0.39, while frequency of SSBs consumption with nutritional status p = 0.481, and independent t-test for SSBs energy contribution with nutritional status p = 0.536. Conclusion: There was no difference in knowledge and Sugar-sweetened beverages (SSBs) consumption in overweight and normal weight adolescents in MAN 2 Surakarta.